NILAI EKONOMI REKREASI TEPIAN SUNGAI BOM LAMA RUMBAI PEKANBARU DENGAN PENDEKATAN TRAVEL COST METHOD - Sujarwo Rio; Mayes Anthoni; Aqualdo Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
In Indonesia, the tourism industry is often considered the answer to various economic problems. So this study aims to find out how much the economic value of Riverside Tourism Bom Lama Rumbai Pekanbaru with the Travel Cost Method approach. In addition, it also aims to determine the effect of age, income, mileage, and travel costs on the number of visits to the Riverside Tourism of Bomb Lama Rumbai Pekanbaru. The location of the research is tourism on the banks of the Sungai Bom Lama Rumbai Pekanbaru in 2021. The method used is descriptive quantitative analysis method. The respondents of this study were 100 people who visited tourist sites on the banks of the Bom Lama Rumbai river, Pekanbaru City. From the calculation of the total cost of travel with the Travel Cost Method is Rp. 86,980. Of this amount there is a contribution of transportation costs is Rp. 34,150 or the equivalent of 39%. While the contribution of consumption costs is Rp. 50,050 or 58% equivalent. The remaining amount of Rp. 2,780 or equivalent to 3%. The data above states that most of the travel costs come from consumption costs. This is because the recreational conditions on the banks of the Old Bomb River have a function as a place to relax for visitors. So that most of the costs incurred are costs related to consumption such as buying snacks, eating, and so on. The economic value obtained from the Rumbai Old Bomb River recreational park in Pekanbaru City is Rp. 478,042,080. So if the tourist location is damaged and is not noticed by the government and the surrounding community, the minimum value that will be a loss is that amount. The results of the analysis of the effect of the influence of age, income, mileage, travel costs on the number of visits to the Bom Lama Rumbai Riverside Tourism Pekanbaru stated that age and income variables, each of which had no effect on the number of visits on the banks of the Bom Lama Rumbai river, Pekanbaru City. So that if the age and income of the visitors increase, it will not change the number of visits to the Sungai Sungai Bom Lama Rumbai Pekanbaru. The distance and cost variables each have a negative effect on the number of visits on the banks of the Bom Lama Rumbai river, Pekanbaru City. So if the distance and travel costs are increasing, it will have the effect of decreasing the number of visits to the Riverside Tourism of the Old Bombay Rumbai Pekanbaru.Keywords : Economic Value, Cost, Tourism